2021
DOI: 10.1038/s41598-021-96076-2
|View full text |Cite
|
Sign up to set email alerts
|

Key features of the environment promoting liver cancer in the absence of cirrhosis

Abstract: The prevalence of obesity and non-alcoholic fatty liver disease (NAFLD) associated hepatocellular carcinoma (HCC) is rising, even in the absence of cirrhosis. We aimed to develop a murine model that would facilitate further understanding of NAFLD-HCC pathogenesis. A total of 144 C3H/He mice were fed either control or American lifestyle (ALIOS) diet, with or without interventions, for up to 48 weeks of age. Gross, liver histology, immunohistochemistry (IHC) and RNA-sequencing data were interpreted alongside hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Tumor development in this murine model was closely associated with the release of different proinflammatory and protumorigenic cytokines such as TNFα and IL6 [ 175 ]. The activation of NF-kB and HCC development is likely to be etiology-independent with our team developing a new dietary-induced HCC experimental model that showed NF-kB activation in the non-tumor tissue of mice developing HCC [ 176 ]. IL6 has also been shown to contribute to hepatocarcinogenesis and a study in HCV patients suggested that this may be gender dependent.…”
Section: Viral Hepatitis Immune Imbalance and Hcc Developmentmentioning
confidence: 99%
“…Tumor development in this murine model was closely associated with the release of different proinflammatory and protumorigenic cytokines such as TNFα and IL6 [ 175 ]. The activation of NF-kB and HCC development is likely to be etiology-independent with our team developing a new dietary-induced HCC experimental model that showed NF-kB activation in the non-tumor tissue of mice developing HCC [ 176 ]. IL6 has also been shown to contribute to hepatocarcinogenesis and a study in HCV patients suggested that this may be gender dependent.…”
Section: Viral Hepatitis Immune Imbalance and Hcc Developmentmentioning
confidence: 99%
“…Mice fed a healthy rodent chow diet had many fewer tumors, but even these were not completely protected after 18 months. Hepatic tumor formation in the context of a high-fat diet and steatosis has been extensively studied and multiple contributing mechanisms are thought to be involved (3,11,16,17). Perhaps among them, the most important is lipotoxicity-driven oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Animals with severe genetic anomalies (14) or animals maintained on a toxic, nutrient-restricted diet such as the methionine-and choline-deficient diet (15) may develop severe liver anomalies more rapidly. When a high-fat or high-fat and -sugar diet alone is utilized in "genetically normal" strains, overt liver damage (beyond steatosis) is not routinely observed before 36 weeks of age (16) and a year or more is required for terminal damage -including hepatocellular carcinoma -to be widely manifested (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this this version posted February 25, 2022. ; https://doi.org/10.1101/2022.02. 24.481779 doi: bioRxiv preprint alone or in combination with the American lifestyle induced obesity syndrome diet (DEN/ALIOS), the latter to establish HCC on a background of NASH 15,16 (Supplementary Data Fig. 1l-o).…”
Section: Pro-tumour Cxcr2 + Neutrophils Associate With Nash-hcc Resis...mentioning
confidence: 99%
“…1h-k ). For an additional autochthonous model, we employed either Diethylnitrosamine (DEN) alone or in combination with the American lifestyle induced obesity syndrome diet (DEN/ALIOS), the latter to establish HCC on a background of NASH 15,16 ( Supplementary Data Fig. 1l-o ).…”
Section: Introductionmentioning
confidence: 99%